Factors influencing tourists’ intention to adopt classified garbage cans in tourism destination - Gong, Yue; Guo, Yan-Ping; Zhai, Shan-Shan; Wong, Philip Pong Weng*; Wang, Lei (Asia Pacific Academy of Science Pte. Ltd., 2024)
Tourists who dispose of their trash properly can reduce the environmental problems caused by careless disposal and improve the effectiveness of recycling reusable things, both of which are essential for the pro-environmental growth of tourist attractions. Therefore, it is critical to classify waste in tourist areas so that travelers can practice pro-environmental activity. Few studies, however, have looked on how tourists feel about adopting classified trash cans in tourist destinations. This study examines the relationship between four types of value (altruistic value, biospheric value, collectivistic value, hedonic value), ecological worldview, three types of images (cognitive image, affective image, overall image) and intention to use classified garbage cans. A total of 407 respondents were collected in Taiyuan Ancient County Town via an online survey. Tests of the proposed hypotheses were conducted using SPSS and AMOS, and results showed that altruistic value, biospheric value and collectivistic value positively influenced ecological worldview, and subsequently, influenced cognitive image and affective image respectively. Affective image influenced overall image, while cognitive image has a significant influence on affective image and on overall image. In addition, hedonic value positively influenced cognitive image, and overall image positively influenced intention to use classified garbage cans. Finally, the theoretical, practical implications and limitations were discussed accordingly.